Development of a Multimedia Courseware Prototype for the Komponen Kesusasteraan Melayu in Bahasa Melayu Subject - Mohammad, Mohamizzam (2006)
KOMSAS (The Malay Literature Component) is a part of The Malay Language school syllabus in Malaysian Secondary school. KOMSAS consist with the elements of traditional and Modern Poems, traditional Prosa, Cerpen, Drama and Novel. Through the literature review and surveys that have been conducted by the researcher, it is shown that there were many obstacles in the process of teaching and learning Malay literature in the classroom. Those obstacles might encounter from the factor of the classroom size and it’s surrounding, ineffective teaching methods delivered by the teachers and the difficulties to visualize the meaning of the literature contents. Therefore, the purpose of this research is to overcome those problems through the development of a multimedia prototype courseware. The prototype is specially developed for the usage of teachers and students who are involved with the subject of KOMSAS. The main objective of this multimedia prototype development is to raise students’ interest towards learning Malay literature through the design of the user interface that is incorporated in the Multimedia interactive courseware of KOMSAS.There are two main modules involved in this development which are the teaching and Learning (P&P) Module and the Exercises Module.A theoretical validation research was conducted on the development of KOMSAS multimedia courseware in order to measure the effectiveness and the efficiency of the multimedia usage. From this research, it is hoped that teachers and students could collaborate together in order to master the Malay Literature and thus put the status of Malay Literature at the highest level using the new and high technology way teaching and learning